New Onset Alacrima as a Presenting Feature of a Skull Base Chondrosarcoma. Issue 6 (November 2020) - Lee, Hanbin; Oliphant, Huw; Vundavalli, Siriram; Taylor, Mark; Koenig, Michael; Hardwidge, Carl; Bucur, Sorin; Rajak, Saul N.
Abstract : Acquired unilateral alacrima as a presenting sign of an intracranial tumor is exceptionally rare, and only described once previously in a case of nasopharyngeal carcinoma. The authors present a 32-year-old female patient who presents with a year-long history of alacrima and arhinorrhea. She was subsequently diagnosed with a petroclival chondrosarcoma extending into Meckel's cave and the cavernous sinus and underwent surgical debulking. To the authors' knowledge, this is the first reported case of acquired unilateral alacrima as a presenting feature of a skull base chondrosarcoma. This case serves to remind general ophthalmologists and oculoplastic surgeons alike that acquired alacrima may be the presenting feature of serious intracranial disease. Abstract : Unilateral acquired alacrima is an exceptionally rare presenting symptom of an intracranial malignancy. We describe a case of a presentation of alacrima in a skull base chondrosarcoma.